Photocatalytic CO2 reduction to syngas using metallosalen covalent organic frameworks - Zhou, Wei; Wang, Xiao; Zhao, Wenling; Lu, Naijia; Cong, Die; Li, Zhen; Han, Peigeng; Ren, Guoqing; Sun, Lei; Liu, Chengcheng; Deng, Wei-Qiao (Nature communications, 2023)
Metallosalen-covalent organic frameworks have recently gained attention in photocatalysis. However, their use in CO 2 photoreduction is yet to be reported. Moreover, facile preparation of metallosalen-covalent organic frameworks with good crystallinity remains considerably challenging. Herein, we report a series of metallosalen-covalent organic frameworks produced via a one-step synthesis strategy that does not require vacuum evacuation. Metallosalen-covalent organic frameworks possessing controllable coordination environments of mononuclear and binuclear metal sites are obtained and act as photocatalysts for tunable syngas production from CO 2 . Metallosalen-covalent organic frameworks obtained via one-step synthesis exhibit higher crystallinity and catalytic activities than those obtained from two-step synthesis. The optimal framework material containing cobalt and triazine achieves a syngas production rate of 19.7 mmol g −1 h −1 (11:8 H 2 /CO), outperforming previously reported porous crystalline materials. This study provides a facile strategy for producing metallosalen-covalent organic frameworks of high quality and can accelerate their exploration in various applications. Here, the authors report a gram-scale, one-step synthesis of metallosalen-covalent organic frameworks (M(salen)-COFs) without vacuum evacuation. M(salen)-COFs exhibit good crystallinity and adjustable activities in CO2 photoreduction to syngas.